Exploring the ‘Dormancy Activation Switch’ in the tumour microenvironment for metastatic lung cancer: The possible role of MicroRNA - Amnani, A.; Siti Fathiah, M/; Teow, Sin Yeang *; Ng, P. Y. (Springer, 2021)
Lung cancer produces the highest mortality rate among cancers, mainly due to its late diagnosis accompanied by single or multiple organ metastasis to the lymph node, pleura, liver, brain and/or bones. In this chapter, we will review the major cellular signalling pathways that promote the proliferation and metastasis of lung cancer cells to each of these metastatic sites, hopefully to shine the light on the possible therapeutic targets that could be developed against these pathways for better therapeutic outcome. Cellular pathways including MAPK, CXCR4/CXCL12, ALK, Rho/ROCK, PI3K and RANK/RANKL signalling will be elaborated in relation to their roles in lymph node, pleura, liver, brain and bone metastasis of lung cancer, respectively. The blooming understanding of microRNA (miRNA) in lung cancer in these recent years has shown that it could play bi-faceted roles in modulating oncogenic pathways. Thus, we also briefly described the candidates of miRNA that may either promote or inhibit the key pathways in lung cancer with various metastatic sites.